Impact of timing of dental implant placement and loading: Summary and consensus statements of group 1—The 6th EAO Consensus Conference 2021. (12th October 2021) - Donos, Nikos; Asche, Nele Van; Akbar, Aron Naim; Francisco, Helena; Gonzales, Oscar; Gotfredsen, Klaus; Haas, Robert; Happe, Arndt; Leow, Natalie; Navarro, Jose Manuel; Ornekol, Turker; Payer, Michael; et al.
Abstract: Objectives: This publication reports on the EAO workshop group 1 summaries, discussions and consensus statements based on four systematic reviews evaluating the impact of timing of dental implant placement and loading. Materials and methods: The first of the systematic reviews was on the influence of the timing of implant placement and loading in the biological outcomes of implant‐supported fixed partial dentures. The second systematic review evaluated the influence of the timing of implant placement and loading on the aesthetic outcomes in single‐tooth implants. The third systematic review was on the long‐term outcomes of maxillary single‐tooth implants in relation to timing protocols of implant placement and loading and the fourth on patient's perception of timing concepts in implant dentistry. The group evaluated these systematic reviews, provided comments and additions as required and agreed on the relevant consensus statements as well as on clinical and research recommendations. Results: Different timings of implant placement/loading presented with high implant survival rates. The systematic reviews evaluated from this working group provided a number of conclusions based on the available/current literature. However, the specific topic of timing is an area that further research is required in order to provide detailed guidelines for the different protocols to be employed.